Pemberdayaan Keluarga Penerima Manfaat (KPM) Program Keluarga Harapan (PKH) Melalui Pelatihan Tata Boga - Hoerudin, Hoerudin; Aulia, Dinda Tasya; Salsabilla, Eliza; Nurlaila, Nurlaila (CV Bayfa Cendekia Indonesia Bekerjasama dengan Jurusan/ Program Studi Pendidikan Masyarakat FKIP Universitas Siliwangi, 2024)
Family empowerment is an effort made as a party to make families more empowered and independent through the skills and abilities possessed by each individual. One of the empowerment programs provided by the Government is the Family Hope Program (PKH). However, in reality there are still many people who depend on PKH, they continue to rely on assistance provided by the government. Based on these problems, the Ciamis Regency Social Service PLP group is interested in carrying out community empowerment for KPM PKH through culinary training. The aim of holding this training is to provide knowledge and skills to PKH members so they can develop their abilities in processing food. The method used is qualitative descriptive. Keywords: Family empowerment, Family Hope Program, Culinary Training